An Investigation of the usage of teaching methods and assessment practices in environmental learning processes and emergent curriculum and sustainability competencies - Mkhabela, Antonia T (Rhodes University, Faculty of Education, Department of Education, 2017)
This study explores the teaching and assessment practices used by teachers in environmental learning processes and emergent curriculum and sustainability competencies. The focus is the school subject Life Sciences in the Further Education and Training Phase. The study is based on four cases of teachers in schools in the Midlands area, in the province of KwaZulu-Natal. Lenses used to review the data included curriculum defined cognitive skills and cognitive levels to review the curriculum competencies and a systems approach to teaching and learning (Wiek, Withycombe, Redman & Mills, 2011) to review emergent sustainability competencies. This study employed qualitative methods, namely a questionnaire, stimulated recall interviews, observations (of lesson plan implementation in classrooms) and document analysis (detailing lesson plans, assessment tasks and learners' work) to generate data. Analysis took place in four phases and included: a descriptive contextual analysis of factors influencing teaching and assessment practices; a descriptive analysis of teacher intentionality, topics, assessment planned and resources used; an analysis of emergent curriculum competencies in informal and formal assessment tasks; and, finally, a second layer of analysis describing emergent sustainability competencies in the environmental learning processes. Ethical considerations included permission for access, anonymity, participant rights and awareness of my role as cluster leader for the group of teachers involved. The study found that the nature of Life Sciences environmental topics and implementation influences the development of curriculum and sustainability competencies. Also, the choice of teaching methods influenced the emergence of particular curriculum and sustainability competencies. The findings also suggested that switching between isiZulu and English, unfamiliarity with action verbs, and the inconsistent use of higher order questions in classroom discussion, informal and formal assessment tasks might have affected success in the development of higher order thinking skills. Finally, the study revealed that environmental learning has the potential to support the development of integrated sustainability competencies. This study was driven by an interest in environmental content knowledge, teaching and assessment within the South African Fundisa for Change network of environmental educators. It is hoped that the study's illustration of how consideration of curriculum and sustainability competencies can contribute to quality education practices in environmental learning, will be of use in this network.
Keywords: Environmental education -- South Africa; Environmental education -- Curricula -- South Africa; Life sciences -- Study and teaching -- South Africa -- Case studies